2020
DOI: 10.18502/kss.v4i4.6467
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Translation Acceptability of Directive Utterances in Harry Potter Novel and the Application in Translation Teaching

Abstract: This article aims at describing the translation acceptability of directive utterances found in Harry Potter novel and its translation in Indonesian and classifying the steps of translation teaching. The data of this descriptive qualitative research were directive utterances found in Harry Potter novel and its Indonesian translation. The data were collected by using content analysis and analyzed using Larson’s and Nababan’s theory of translation acceptability. The first finding shows that directive utterances t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…It also involves making sure that the target language is accurate so that readers can easily understand the meaning. According to (Harjanti, 2020), the degree of accuracy or message equivalency that may be attained in translated texts is determined by how well the author's style, the context of the text, and the language used in the translation all fit together. While analyzing the data for this theme, we found that most of the students who participated in this research strongly agree that the translation results in U-Dictionary are accurate compared to the results from Google Translate.…”
Section: Theme One: An Accurate Translationmentioning
confidence: 99%
“…It also involves making sure that the target language is accurate so that readers can easily understand the meaning. According to (Harjanti, 2020), the degree of accuracy or message equivalency that may be attained in translated texts is determined by how well the author's style, the context of the text, and the language used in the translation all fit together. While analyzing the data for this theme, we found that most of the students who participated in this research strongly agree that the translation results in U-Dictionary are accurate compared to the results from Google Translate.…”
Section: Theme One: An Accurate Translationmentioning
confidence: 99%